Women, children and the calculation of labour productivity in Europe and North America - Craig, Béatrice (Université d'Ottawa | University of Ottawa, 2000)
Economic historians have viewed increases in agricultural labour productivity as one of the key factors behind the shift from an agrarian to an industrial economy. It allowed rural regions to "release" workers for the factoy. Jan De Vries suggested that in the XVIIth and XVIIIth century, women and children may have been the workers whose productivity increased the most. This made women and children central agents in the process of economic transformation. However, calculating labour productivity is fraught with difficulties and the problems are worse in the case of women and children's productivity. Some of the assumptions underpinning the calculations of economic historians are more fragile when applied to women and children than to men. Economic historians have at times assumed that censuses provided reasonably accurate estimates of the size of the labour force; that the participation rates were uniform within the different categories, and that women and children were as free as men responded to the incentives of the market. All those proved false, and this should incite researchers to extreme caution.